2016
DOI: 10.1080/10790268.2016.1224215
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical characteristics of persons with spinal cord injury in Turkey: One-year experience of a primary referral rehabilitation center

Abstract: The mean age of SCI population is increasing. Falls constitute the majority of etiologic factors and are more common in persons >60 years old. More than 20% of falls from a height are related to occupational injury. Male-female ratio is decreasing. Thoraco-lumbar injures are more common than cervical injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…According to previous reports, the incidence rate of TSCI worldwide is 2.3 ( 2 ) to 150.6 ( 3 ) per million per year. In this survey, the incidence of TSCI was 49.8 per million per year in China, which was higher than that in most previous findings ( 6 8 , 10 , 21 , 26 , 35 44 , 46 , 47 ), but lower than that in other studies ( 3 , 5 , 9 , 32 34 , 45 , 48 ). The incidence of TSCI in this survey increased with age before 75 years old.…”
Section: Discussioncontrasting
confidence: 81%
“…According to previous reports, the incidence rate of TSCI worldwide is 2.3 ( 2 ) to 150.6 ( 3 ) per million per year. In this survey, the incidence of TSCI was 49.8 per million per year in China, which was higher than that in most previous findings ( 6 8 , 10 , 21 , 26 , 35 44 , 46 , 47 ), but lower than that in other studies ( 3 , 5 , 9 , 32 34 , 45 , 48 ). The incidence of TSCI in this survey increased with age before 75 years old.…”
Section: Discussioncontrasting
confidence: 81%
“…12,[19][20][21]34,35 Most articles reported a lower percentage of complete injury than incomplete injury, except 4 studies. 16,17,32,36 In our review, when classifying the types of disabilities caused by SCI, the tetraplegia was more common than paraplegia in both developed countries and nondeveloped countries except Turkey 14 and Canada. 37 Motor-complete injuries (America Spinal Injury Association Impairment Scale [AIS]-A or -B) were more common for patients with traumatic SCI, while there were more motorincomplete injuries (AIS-C or-D) for patients with NTSCI.…”
Section: Level and Severity Of Injurymentioning
confidence: 80%
“…However, the most common cause of SCI in nondeveloped countries was still falls. [11][12][13][14][15][16][17][18] incidence The incidence rate represents the ratio of a new disease in a particular population during a certain period of time. With the expansion of human activities, the incidence of SCI also increased gradually ( Table 1).…”
Section: Results Etiologymentioning
confidence: 99%
“…In this regard, average age (43.8 years) and male/female ratio (1.39/1) in our cohort seem to support a prolonged life expectancy in SCI patients with a shift to a higher prevalence in the elderly population 2,3,10,36,38-40 alongside a decline in the male/female ratio for SCI over time. 32,36,40 Published reports on factors influencing QOL in SCI patients revealed inconsistent findings. 41 Severity of impairment, duration of injury, age, sex, race, marital and educational status, medical complications, self-perceived health and mobility were reported to be associated with QOL in some studies, [41][42][43][44][45][46] while others reported no such associations.…”
Section: Discussionmentioning
confidence: 99%